2000
DOI: 10.3141/1723-17
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt Mix Evaluations: Case Study at San Francisco International Airport

Abstract: A forensic study of asphalt mix performance at the San Francisco International Airport (SFIA) using the simple shear test developed by the Strategic Highway Research Program is described. The study examined taxi ways subjected to stationary and slow movements of heavy aircraft wheel loads and covered a period of about 2.5 years. The results of the study indicate the need to modify (or change) current FAA criteria for mix design of asphalt mixes for heavy-duty airfield pavements, particularly for taxi ways used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Historically, various airfield pavements have experienced severe asphalt rutting because of the selection of inadequately soft binders. A well-known case is that of the San Francisco International Airport ( 22 ), where investigations concluded that the soft binder, slow-moving traffic, and the high tire pressure of the Boeing 747-400 aircraft contributed to rutting distortions that occurred at the airfield ( 23 , 24 ). Additional occurrences of early-life asphalt rutting were also detected in several airports around the world, particularly busy airports in hot climates, such as those in Dubai, Kuala Lumpur, and several airports in Australia ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, various airfield pavements have experienced severe asphalt rutting because of the selection of inadequately soft binders. A well-known case is that of the San Francisco International Airport ( 22 ), where investigations concluded that the soft binder, slow-moving traffic, and the high tire pressure of the Boeing 747-400 aircraft contributed to rutting distortions that occurred at the airfield ( 23 , 24 ). Additional occurrences of early-life asphalt rutting were also detected in several airports around the world, particularly busy airports in hot climates, such as those in Dubai, Kuala Lumpur, and several airports in Australia ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%